2017
DOI: 10.2147/ijgm.s134095
|View full text |Cite
|
Sign up to set email alerts
|

The role of smartphones in encouraging physical activity in adults

Abstract: Lack of physical activity is a global public health issue. Behavioral change interventions utilizing smartphone applications (apps) are considered a potential solution. The purpose of this literature review was to: 1) determine whether smartphone-based interventions encourage the initiation of, and participation in, physical activity; 2) explore the success of interventions in different populations; and 3) examine the key factors of the interventions that successfully encouraged physical activity. Eight databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 41 publications
1
54
0
Order By: Relevance
“…It also reported that the programs functioned positively for the thoughts, perceptions, strategies, and motivation to promote physical activity. According to the results of the review paper by Stuckey et al, [29], eight out of 18 studies applying smartphone-based interventions showed an increase in physical activity or steps. For young adults, we believed that as smartphone apps are able to always be with them, they could be effective behavior change support systems.…”
Section: Discussionmentioning
confidence: 99%
“…It also reported that the programs functioned positively for the thoughts, perceptions, strategies, and motivation to promote physical activity. According to the results of the review paper by Stuckey et al, [29], eight out of 18 studies applying smartphone-based interventions showed an increase in physical activity or steps. For young adults, we believed that as smartphone apps are able to always be with them, they could be effective behavior change support systems.…”
Section: Discussionmentioning
confidence: 99%
“…We did not restrict year of publication, but we did restrict language to English or German. Furthermore, we searched reference lists of published reviews on the topic [13,14,18] and posted invitations to research communities in health psychology, sport psychology, social psychology, and sport science to contribute relevant studies.…”
Section: Searching For Studiesmentioning
confidence: 99%
“…In the domain of physical activity, mHealth interventions yield small to moderate effects [12], but so far, researchers were not able to pinpoint contextual elements that lead to greater intervention success in increasing PA [12][13][14][15][16][17][18]. Indeed, a wide range of interventions are implemented that often overlap with each other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article by Stuckey et al 1 entitled “The role of smartphones in encouraging physical activity in adults” recently published in the International Journal of General Medicine .…”
mentioning
confidence: 99%